2019
DOI: 10.1155/2019/6198067
|View full text |Cite
|
Sign up to set email alerts
|

Pinelliae Rhizoma Praeparatum Cum AlumineExtract: Sedative and Hypnotic Effects in Mice and Component Compounds

Abstract: Pinelliae Rhizoma Praeparatum Cum Alumine (PRPCA) is useful for eliminating dampness and phlegm in clinical settings, targeting the main mechanisms of insomnia as defined in traditional Chinese medicine. However, little is known regarding the sedative and hypnotic effects of PRPCA. In the present study, we examined the sedative effects of PRPCA via a locomotor activity test and aimed to determine the most appropriate concentration of PRPCA for achieving these effects. The strongest sedative effects were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Cavidine (alkaloid) and GA (fatty acids) were identified as the core active components linked with the highest number of targets, as alkaloids and fatty acids appear to play an important role in meliorating sleep quality by ascending rapid eye movement sleep and descending sleep fragmentation. [30] The molecular docking results also confirmed that these 2 components exhibited good binding affinity to the hub target genes. It has been reported that cavadine, which is an alkaloid, may extend the circadian period by enhancing RORα function and prolonging the molecular circadian clock period by raising the stability of the PER2 protein in the suprachiasmatic nucleus.…”
Section: Discussionmentioning
confidence: 70%
“…Cavidine (alkaloid) and GA (fatty acids) were identified as the core active components linked with the highest number of targets, as alkaloids and fatty acids appear to play an important role in meliorating sleep quality by ascending rapid eye movement sleep and descending sleep fragmentation. [30] The molecular docking results also confirmed that these 2 components exhibited good binding affinity to the hub target genes. It has been reported that cavadine, which is an alkaloid, may extend the circadian period by enhancing RORα function and prolonging the molecular circadian clock period by raising the stability of the PER2 protein in the suprachiasmatic nucleus.…”
Section: Discussionmentioning
confidence: 70%
“…Modern scientific research provided evidence that WDT contains compounds including flavonoids, phenols, alkaloids, triterpenoid organic acid, polysaccharides, and phosphodiesterase inhibitors ( Table 3 ), which have been found to possess neuroprotective, neuromodulation, anti-mutagenic, antioxidant, antiemetic, antithrombotic, antipyretic, and anti-inflammatory effects [ 2 , 30 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous extract solution was concentrated to a volume of 100 mL. Finally, the extract solution was filtered using a standard test sieve of 150 μm, freeze-dried and maintained in desiccators at 4°C until use [21,22].…”
Section: Preparation Of Freeze-dried Radix Astragali and Radix Angelimentioning
confidence: 99%